Effects of Ultrasound-Assisted Soy Lecithin Addition on Rehydration Behavior and Physical Properties of Egg White Protein Powder - Sijia Cao; Xuanting Liu; Zhiyuan Zheng; Zhaohui Yan; Ting Zhang; Jingbo Liu; Ting Yu (Foods, 2024)
This study investigated the effects of ultrasound-assisted soybean lecithin (SL) on the rehydration behavior and physical properties of egg white protein powder (EWPP) and its ability to enhance the efficacy of EWPP instant solubility. The results of rehydration, including wettability and dispersibility, indicated that ultrasound (200 W)-assisted SL (5 g/L) addition had the shortest wetting time and dispersion time, which were 307.14 ± 7.00 s and 20.95 ± 2.27 s, respectively. In terms of powder properties, the EWPP with added SL had lower lightness, moisture content and bulk density. In addition, the increase in average particle size, net negative charge, free sulfhydryl group content and surface hydrophobicity indicated that ultrasound treatment facilitated the protein structures unfolding and promoted the formation of SL-EWP complexes. Overall, our study provided a new perspective for the food industry regarding using ultrasound technology to produce instant EWPP with higher biological activity and more complete nutritional value.